24.3: Adaptive Optimization of Rendering for Multi‐Projector‐Type Light Field Display. Issue 1 (June 2015) - Zhong, Qing; Li, Haifeng; Liu, Xu; Chen, Beishi; Xu, Liang
Abstract : An adaptive optimization in rendering process for multi‐projection‐type light field display is proposed. The optimization smoothed the scene that away from the screen to reduce the distortion, without affecting the scene that near the screen. Comparison shows that the optimization enhanced the overall display quality of the scene.